Pengaruh Brand Image, Brand Love Dan Brand Trust Terhadap Keputusan Pembelian Sepatu Adidas (Studi Pada Mahasiswa FEB Universitas Islam Malang) - Faisol, Amir; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze the impact of brand image, brand love and brand trust on purchasing decisions for Adidas shoes. Using multiple linear regression methods, this research focuses on explanatory research with a quantitative approach. The research sample of 85 consumers was taken using the Malhotra formula. Data analysis was carried out with the help of SPSS version 25 software, including validity test, reliability test, normality test, classical assumption test, hypothesis test, and R2 coefficient of determination test. The research results show that overall, brand image, brand love and brand trust have a simultaneous or partial influence on consumer purchasing decisions for Adidas shoes. Keywords: Brand Image, Brand Love, Brand Trust, Purchase Decisions